The facilitators and barriers associated with implementation of a patient-centered medical home in VHA. (December 2015) - Helfrich, Christian; Sylling, Philip; Gale, Randall; Mohr, David; Stockdale, Susan; Joos, Sandra; Brown, Elizabeth; Grembowski, David; Asch, Steven; Fihn, Stephan; Nelson, Karin; Meredith, Lisa
Abstract Background The patient-centered medical home (PCMH) is a team-based, comprehensive model of primary care. When effectively implemented, PCMH is associated with higher patient satisfaction, lower staff burnout, and lower hospitalization for ambulatory care-sensitive conditions. However, less is known about what factors contribute to (or hinder) PCMH implementation. We explored the associations of specific facilitators and barriers reported by primary care employees with a previously validated, clinic-level measure of PCMH implementation, the Patient Aligned Care Team Implementation Progress Index (Pi2 ). Methods We used a 2012 survey of primary care employees in the Veterans Health Administration to perform cross-sectional, respondent-level multinomial regressions. The dependent variable was the Pi2 categorized as high implementation (top decile, 54 clinics, 235 respondents), medium implementation (middle eight deciles, 547 clinics, 4537 respondents), and low implementation (lowest decile, 42 clinics, 297 respondents) among primary care clinics. The independent variables were ordinal survey items rating 19 barriers to patient-centered care and 10 facilitators of PCMH implementation. For facilitators, we explored clinic Pi2 score decile both as a function of respondent-reported availability of facilitators and of rating of facilitator helpfulness. Results The availability of five facilitators was associated with higher odds of a respondent's clinic's Pi2 scores being in the highest versus lowest decile: teamlet huddles (OR = 3.91), measurement tools (OR = 3.47), regular team meetings (OR = 2.88), information systems (OR = 2.42), and disease registries (OR = 2.01). The helpfulness of four facilitators was associated with higher odds of a respondent's clinic's Pi2 scores being in the highest versus lowest decile. Six barriers were associated with significantly higher odds of a respondent's clinic's Pi2 scores being in the lowest versus highest decile, with the strongest associations for the difficulty recruiting and retaining providers (OR = 2.37) and non-provider clinicians (OR = 2.17). Results for medium versus low Pi2 score clinics were similar, with fewer, smaller significant associations, all in the expected direction. Conclusions A number of specific barriers and facilitators were associated with PCMH implementation, notably recruitment and retention of clinicians, team huddles, and local education. These findings can guide future research, and may help healthcare policy makers and leaders decide where to focus attention and limited resources.